Local Food, Centralized Governance, and the Limits of Policy Localization in Indonesia’s Free Nutritious School Meal Program: Evidence from Sumba - Stepanus Makambombu (Pusbindiklatren Bappenas, 2026)
The Free Nutritious Meal Program (Makan Bergizi Gratis/MBG) seeks to improve schoolchildren’s nutrition while stimulating local economies through the use of local food. However, evidence from Sumba reveals a structural tension between policy localization and centralized governance. Using a qualitative case study across three districts, based on interviews, observation, and document analysis, this study finds that program implementation is driven more by centralized control and political dynamics than by local capacities. As a result, menus remain dominated by rice and market-based commodities, marginalizing locally adaptive savanna foods. This reflects an epistemological disconnection between standardized nutrition frameworks and local food knowledge. While MBG improves short-term attendance and learning readiness, its long-term contribution to local food systems is limited. Policy effectiveness requires concrete reforms: greater local decision-making authority, formal recognition of local food systems in nutritional standards, and integration of local producers into supply chains. Without these, MBG risks reinforcing dependency on external food systems.